CONTRIBUIÇÃO PARA O CONHECIMENTO DO Agathomerus sellatus GERM. (COL., MEGALOPODIDAE) - Tella, Romeu de (REVISTA DE AGRICULTURA, 2016)
CONTRIBUIÇÃO PARA O CONHECIMENTO DO Agathomerus sellatus GERM. (COL., MEGALOPODIDAE)